Giant chancre in an octogenary patient. Always remember syphilis! - Ramos, Mauro Cunha; Ruwel, Andressa Goldman (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Syphilis is a sexually transmitted infection (STI) caused by the Treponema pallidum and has become epidemic in the past two decades. The disease is often asymptomatic, and its manifestations are diverse. It may affect multiple systems, posing the risk of serious consequences or even death. Objective: To present a case of an exuberant syphilis-related lesion in an elderly man. Case report: An 85-year-old man presented with a painless penile lesion. He reported having had oral sexual contact (felatio) with a female sex worker six weeks prior the presentation of the lesion. During the physical exam, an ulcer measuring three to four cm was observed, reaching subcutaneous tissue down to the Buck’s fascia, and presenting a clean beefy red base, and an infiltrated edge. Bilateral and movable enlarged and painless lymph nodes were found. The rapid immunochromatographic test was positive for syphilis and negative for HIV, hepatitis B, and hepatitis C. Treatment consisted of an in loco injection of 2,400,000 IU of benzathine penicillin. Conclusion: In spite of being more common among younger individuals, syphilis should be always considered in the differential diagnosis of genital ulcers, regardless of the patient's age. Many aged people keep an active sexual life especially with the increase of longevity and effective therapeutic measures for erectile disfunction. The false belief that sexual activity ceases to exist in older age groups must, therefore, be abandoned.